Does primary biliary cirrhosis cluster in time?. (July 2015) - Muirhead, Colin R.; James, Oliver F.W.; Ducker, Samantha J.; McNally, Richard J.Q.
Highlights: This is the first study to look for irregular temporal patterns in diagnoses of PBC. There was no evidence for general irregular (non-seasonal) temporal clustering. There was long-term temporal variation in PBC diagnoses. Agents occurring in geographically widespread mini-epidemics are not implicated. Future work should look for agents occurring in localised sporadic mini-epidemics. Abstract: The aetiology of primary biliary cirrhosis (PBC) is not well established. Previously we found evidence of space–time clustering and seasonal variation in the date of diagnosis, suggesting a possible role for a transient or seasonally varying environmental factor. We examined whether a temporally varying environmental agent may be involved by analysing population-based PBC data from northeast England over 1987–2003. Using an adaptation of a method proposed by Potthoff and Whittinghill, we found significant temporal variation by date of diagnosis at the level of aggregation of one year. However, there was no evidence for general irregular (non-seasonal) temporal clustering within periods less than a year. These results provide little support for the involvement of agents occurring in geographically widespread mini-epidemics, but – taken together with studies of spatial and spatio-temporal clustering – do not preclude the role of more localised sporadic mini-epidemics. Future research should seek to elicit putative environmental agents.